THE ACCRETION MODES OF THE ASYNCHRONOUS POLAR BY CAM AT DEFINITE BEAT PHASES FOR THE LOW ACCRETION STATE - Babina, Ju.; Pavlenko, E. P.; Andreev, M. (Одеські астрономічні публікації, 2017)
The results of photometric observations of asynchronous polar of BY Cam in the low accretion state are presented. It was succeeded to show on the basis of plenty of observant material, that the type of curves of brightness depends on the phases of synodical cycle, id est. from the orientation of accretion areas to the red dwarf, but not changes chaotically from a cycle to the cycle. After the grouping of curves of brightness on the phases of synodical period appeared, that the profiles of curves of brightness recur through 1/2 cycles of beating period.